Induction of Trichosanthes cucumerina anguina L. var (L. Haines) Hairy Roots Using Agrobacterium rhizogenes ATCC 15834 for Production of Bioactive Protein - . CHURIYAH; GUSTAF ADOLF WATTIMENA; BAMBANG PONTJO PRIYOSOERYANTO (Microbiology Indonesia, 2011)
In the recent years, hairy roots have become a useful model system for the study of bioactive secondary molecule production and protein expression. Hairy roots of Trichosanthes cucumerina var. anguina were obtained by direct inoculation of the plantlet with Agrobacterium rhizogenes ATCC 15834 strain agropine. Six root clones of Trichosanthes cucumerina var. anguina hairy roots TH1, TH2, TH3, TH4, TH6, and TH8 were obtained from the induced hairy roots. The hairy root proteins were extracted with phosphate buffer saline, then fractionated by ammonium sulphate precipitation (80%), dialysis, and gel filtration. The toxicity of the proteins was analyzed using brine shrimp lethality test followed by cytotoxicity test (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide assay) using HeLa and K-562 cancer cell line. The TH2 root clone showed the highest protein yield (0.83%) and most toxic on BSLT with Lethal Concentration 50 was 5.76 μg mL-1. PCR analysis indicated the integration of rolB gene to the genome of TH2 root clone which was showed by a DNAband of 780 bp on the electrophoretic agarose gel. Protein fractionation of the TH2 root clone resulted in four fractions, one of which the-TH2-3 protein fraction revealed the highest yield (0.29%) and toxicity on BSLT with  LC50 up to 0.92 μg mL-1 . The Cytotoxicity test of the TH2 protein and TH2-3 protein fraction indicated that both of proteins inhibited the proliferation of Hela and K-562 cell withLC up to 49 μg mL-1.